Distribution of phenolics in various Malaysian medicinal plants - Jamal, Parveen; Ahmad Barkat, Anumsima; Amid, Azura (Asian Network for Scientific Information, 2010)
Phenolics, which are widely distributed in plant kingdom, appear to have desirable medicinal properties and play a major role in both plant and animal health. Some have been reported to be antitumor agents and to exhibit antiviral and antimicrobial activities, hypotensive effects and antioxidant properties. These compounds, either as isolates or in conjunction with other compounds, may be used for various health benefits. In this study, forty types of Malaysian medicinal plants were examined to develop an understanding of the distribution of phenolics and to give an assessment of the diversity present in the selected plants. The selection of plants was based on their frequent usages by local folks for their medicinal benefits. Total phenolic content was analyzed by Folin and Ciocalteau’s phenol reagent and their concentration was expressed as Gallic Acid Equivalent (GAE). All plant samples gave positive result with varying concentrations. Highest amount was obtained from Piper betle L. which had phenolic content of 8986.67 mg L-1 GAE, while the lowest concentration of 133.33 mg L-1 GAE was obtained from Canna indica Linn. This information can be used to assess taxonomic classifications, evaluate potential sources of phenolic compounds for agricultural and pharmaceutical uses and evaluate breeding program results.